2010
DOI: 10.2220/biomedres.31.89
|View full text |Cite
|
Sign up to set email alerts
|

Invasive micropapillary variant of the gallbladder adenocarcinoma and its aggressive potential for lymph node metastasis

Abstract: An invasive micropapillary variant (IMPV) has recently been described in several organs but has not been reported in the gallbladder. It has been mentioned to have aggressive behavior with a high propensity for lymphovascular invasion, lymph node metastasis and poor clinical outcome. We analyzed the clinicopathologic findings of IMPV and compared them with those of a conventional adenocarcinoma in the gallbladder to clarify the highly aggressive potential of IMPV of gallbladder carcinoma. Ninety consecutive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…IMPC has been reported in various organs, including the breast [1], lung [2], parotid gland [3], ovary [5], pancreas [6], gallbladder [7], and stomach [8]; however, reports of colorectal micropapillary carcinoma, especially in early stages, are rare.…”
Section: Introductionmentioning
confidence: 99%
“…IMPC has been reported in various organs, including the breast [1], lung [2], parotid gland [3], ovary [5], pancreas [6], gallbladder [7], and stomach [8]; however, reports of colorectal micropapillary carcinoma, especially in early stages, are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The previous reports revealed that IMPC exhibited a tendency for lymphatic invasion and lymph node metastasis. In our study, IMPC component of extrahepatic bile duct ranged from 5 to 60% of the entire tumor, while with IMPC components were found in the other organs: 10–90% in salivary duct carcinoma (15), 10–90% in gastric carcinoma (21), 5–10% in gallbladder carcinoma (17), 5–95% in breast cancer (27). IMPC component, regardless of its tumor volume, has been shown to have malignant potential for lymphatic invasion and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 50%
“…Recent studies have demonstrated that an invasive micropapillary carcinoma (IMPC) frequently shows aggressive tumor behaviors with marked lymph-vascular invasion, resulting in poor prognosis in several organs including the breast (3–5), urinary bladder (68), lung (913), parotid gland (14,15), pancreas (16), gallbladder (17), colorectum (18) and stomach (1922). To the best of our knowledge, however, there has been only one case report of extrahepatic bile duct carcinoma which contains IMPC (23).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the majority of patients have frequent recurrences after the surgery, and pursue the chemotherapy or radiotherapy treatment when recurrences happened after the surgery (2, 15). Several previous studies have demonstrated high risks of disease progression, using surgically-resected GBC cases, and histological grade, depth of wall infiltration, and lymph node status have been determined to be clinicopathological prognostic factors (6,22). In addition, we have classified the wall-invasion pattern of GBC into two groups, i.e., infiltrative growth type (IG type) and destructive growth type (DG type) (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%